PENGARUH PERSEPSI LITERASI KEUANGAN, KEMANFAATAN, KEMUDAHAN, DAN RISIKO TERHADAP MINAT GENERASI Z DALAM MENGGUNAKAN QRIS - Alma Nabila Kuntoro Putri; Amelia Setiawan; Hamfri Djajadikerta (LPPM Universitas Ekasakti, 2024)
This research focuses on analyzing whether there is an influence of perceptions of financial literacy, usefulness, ease of use, and risk on Generation Z's interest in using QRIS. The research method used is quantitative, with data obtained through a Google Form questionnaire, resulting in 203 respondents. IBM SPSS Statistics 26 was used to process 150 samples, with a confidence level of 95% and a margin of error of 5%. The tests conducted included validity, reliability, normality, heteroscedasticity, multicollinearity, regression, partial tests (t-test), simultaneous tests (f-test), and finding the adjusted R². Previous research had similarities in the dependent variables, namely perceptions of financial literacy, usefulness, ease of use, and risk, while the update is the different dependent variable, which is Generation Z's interest in using QRIS. From the hypothesis testing results, it was concluded that perceptions of financial literacy, usefulness, ease of use, and risk have an influence on Generation Z's interest in using QRIS. The results of this study can be a consideration for those who want to research further with the same variables to compare with existing literature findings. Additionally, it can enhance readers' knowledge about factors that can increase interest in using QRIS.